In-Depth Profiling of T-Cell Responsiveness to Commonly Recognized CMV Antigens in Older People Reveals Important Sex Differences - Reus, Bernhard; Caserta, Stefano; Larsen, Martin; Morrow, George; Bano, Aalia; Hallensleben, Michael; Rajkumar, Chakravarthi; Pera, Alejandra; Kern, Florian (Frontiers in Immunology, 2021)
The impact of biological sex on the immune response to Cytomegalovirus (CMV) remains relatively unexplored. Only one study has previously compared CMV-specific T-cell responses in men and women. Many studies, however, have shown an association between CMV infection and immunosenescence with broad effects on peripheral blood lymphocyte subsets as well as the T and B-cell repertoires. Here we examine the T-cell response to 16 CMV proteins in great detail, one by one, in women and men in order to elicit potential differences that may help explain hitherto unexplained CMV-associated, sex-specific pathologies. T-cell responses to CMV antigens were examined in 94 older CMV-seropositive individuals (60 to 93 years) with respect to 16 different CMV proteins arranged in 14 stimulation pools. Flow-cytometry was used to assess CD4 and CD8 T-cell reactivity by enumerating IFN-γ, TNF, and IL-2 positive cells by intracellular cytokine staining, after in vitro stimulation with CMV-antigens. Viral antigen-specific responses were evaluated in terms of each cytokine separately or in terms of cytokines produced simultaneously (polyfunctionality), in parallel to surface phenotype and CD3 downmodulation. We used the polyfunctionality index and a memory subset differentiation score to analyze associations between response size, cytokine production, polyfunctionality, and memory subset distribution. No sex differences were found with respect to CMV target protein selection, however, in men the T-cell response appeared more focused and accompanied by a more prominent accumulation of CMV-specific memory CD4 and CD8 T-cells. T-cell polyfunctionality and differentiation were similar in the sexes, however, CMV-specific T-cells in men produced more pro-inflammatory cytokines. Particularly, TNF production by CD4 T-cells was stronger and showed more outliers in men than in women. Also, men had on the whole larger responses to CMV proteins with immediate early/early kinetics. Mechanistically, our data support that, preferentially in men, CMV reactivation might drive bigger and more dominant CD4 T-cell responses, mirrored by skewed patterns of CD3 downmodulation. In conclusion, the CMV-specific T-cell response in men is generally larger and more pro-inflammatory than in women, featuring a larger number of outliers, in particular CD4 T-cell responses producing TNF. These findings may help explain sex differences in CMV-associated pathologies.